THE STRATEGY OF SATLANTAS POLRESTABES SURABAYA TO REALIZE A TRAFFIC ORDER AT SURABAYA CITY - Gedeon Firnandus Ulaan; Diana Hertati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
This research is motivated by there are still have a number of accidents that happened on the streets in Surabaya City. The accidents make a lot of disadvantages as material loss and fatalities. It is caused by unorderly society in this case, traffic order. Lack of social awareness and less extensive action from the police was attention to realize a traffic order. It is necessary to do for a city like Surabaya City. The purpose of this research is to describe and to analyze the strategy of the Surabaya police traffic unit to realize a traffic order at Surabaya City. This research used descriptive qualitative methods by observing, interviewing, and documenting. The results of this study indicate that the preemptive strategy carried out by Satlantas Polrestabes Surabaya has not been maximized. The preventive strategy has been carried out properly so that it can prevent people from committing violations which are potentially become accidents. The repressive strategy has been carried out properly too. From the three things above, only the preemptive strategy has not been maximized. Meanwhile, preventive and repressive strategies must be maintained and even improved to create an orderly and zero accident society.